Clinical and Cephalometric Assessments in Grade II and Grade IV Adenoid Hypertrophy: A Cross-Sectional Study - Razaq, Afnan R.; Saloom, Hayder F. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Adenoid hypertrophy is one of the most common causes of nasal obstruction, and physicians use different methods to investigate it to reach a definite diagnosis. Objectives: This study aims to determine whether there are clinical differences between grade II and IV adenoid hypertrophy and whether there is a positive correlation between adenoid-nasopharyngeal ratio and endoscopic examination findings.Methods: This study was carried out on 120 patients; they were confirmed with five clinical tests (graded mirror, water-retention, lip-seal, deep-breath, and functional tests) and lateral cephalometric radiographs to measure the adenoid-nasopharyngeal ratio. Kruskal-Wallis test was used for the mirror test, while the Chi-squared test was used for the rest to detect the differences among groups. Spearman's correlation coefficient test was used to determine the correlation between the adenoid-nasopharyngeal ratio and endoscopic findings.Results: The age range of the patients was 6-12 years [mean age = 9.13 ± 1.97 years], 60.8% male, 39.2% female. Kruskal-Wallis and Chi-squared tests showed a statistically significant difference with P > 0.01 between groups. A strong positive significant correlation at P < 0.01, Spearman's test 0.94 was found between adenoid-nasopharyngeal ratio and endoscopic findings.Conclusion: Lateral cephalogram and nasal endoscopy can detect most pathologies associated with airway blockage. There are clinical differences between grade II and grade IV adenoid hypertrophy, and there is a good correlation between the adenoid-nasopharyngeal ratio measured by lateral cephalogram and endoscopic findings.